Конституційна реформа України 2016 року та її вплив на розвиток правової системи держави - Гончаренко, Л. Л.; Honcharenko, L. L. (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 2 (101), ч. 2. - С. 24-29, 2023)
Спираючись на аналіз наукових поглядів учених, визначено поняття Конституції України як Основного Закону нашої країни. Розкрито зміст і значення конституційної реформи. На основі аналізу змін до чинного законодавства взагалі та Конституції України зокрема надано оцінку впливу конституційної реформи України 2016 року на розвиток правової системи держави.

It has been established that the constitution is the fundamental law of any modern state, which ensures the integrity of the country's legal system. The said legal act contains the most important provisions defining the basic guarantees for the protection of rights, freedoms and interests of a person and a citizen, as well as the key principles of functioning of the State as a whole and its legislative, executive and judicial branches. It is noted that the priority of the constitutional provisions is due to the fact that all other legal acts of different legal force are developed in accordance to it. Attention is drawn to the fact that the constitutional reform in Ukraine implemented in 2016 was important for our country, since: firstly, it was aimed at strengthening democracy and observance of the rule of law in Ukraine; secondly, the powers of the President of Ukraine and the Verkhovna Rada of Ukraine to elect judges to office were adapted in accordance with international standards; thirdly, the requirements for the personality and professionalism of judges were significantly increased. It has been noted that the constitutional reform of 2016 had a significant impact not only on the activities of the judiciary, but also on the development of the legal system of the Ukrainian State. Thus, among the positive aspects of the relevant reform are the following: the content of the legal provisions enshrined in the Constitution of Ukraine defining human rights and freedoms has become one of the broadest among European countries; the reform significantly changed the approach to the content of the principle of judicial immunity, in particular, a functional approach to ensuring judicial immunity was applied; the activities of the bodies responsible for the judiciary were reformed in accordance with European requirements and standards.

Опираясь на анализ научных взглядов ученых, определено понятие Конституции как Основного Закона нашей страны. Раскрыты смысл и значение конституционной реформы. На основе анализа изменений в действующее законодательство вообще и Конституции Украины, в частности, дана оценка влияния конституционной реформы Украины 2016 года на развитие правовой системы государства.
Constitutional reform of Ukraine in 2016 and its impact on the development of the legal system
Keywords: конституція; Конституція України; конституційна реформа; судді; судочинство; правова система; constitution; Constitution of Ukraine; constitutional reform; judges; justice; legal system; конституция; Конституция Украины; конституционная реформа; судьи; судопроизводство; правовая система